PENGALAMAN EMOSIONAL DAN PROSES REFLEKTIF PEMBACA DALAM NOVEL SEPORSI MIE AYAM SEBELUM MATI DAN SISI TERGELAP SURGA - Altisha Nabila Pratiwi (Universitas Pendidikan Muhammadiyah Sorong, 2026)
This study aims to analyze the emotional experiences and reflective processes of readers in two novels by Brian Khrisna, Seporsi Mie Ayam Sebelum Mati (2025) and Sisi Tergelap Surga (2023), and to examine the role of literature as a medium for emotional literacy. The method used is a qualitative descriptive approach with textual and reader response analysis. The research data consist of narrative and dialogue excerpts that elicit readers’ emotional experiences, while secondary data are obtained from reader reviews on online platforms. Jauss’s and Iser’s reader-response theories serve as the main framework to interpret the interaction between readers and the text, while LaCapra’s trauma theory and Jakobson’s concept of the dominant are used to explain affective mechanisms and the influence of emotional elements in the reading experience. The results show that both novels create a reflective space where readers undergo a process of working through, namely, the processing and acceptance of emotional wounds through identification with characters and narratives. Emotion, as the dominant in Khrisna’s works, becomes the main driver of this experience, so that readers not only interpret the text but also undergo a reflective process that allows them to understand and organize emotions symbolically. These findings affirm that contemporary literature can serve as a means of self-healing and emotional literacy, while also offering important considerations for developing literary policies that support the psychological well-being of readers. KEYWORDS: Seporsi Mie Ayam Sebelum Mati; Sisi Tergelap Surga; Reader Reception; Trauma; Self-healing; Emotional Literacy